Kamień – świadek przymierza w Sychem (Joz 24,1-28) - Florczyk, Łukasz (Verbum Vitae, 2015)
Stones have been commonly used in everyday life of people living in Canaan. They have also been witnesses of important events in the history of the Chosen People and have been bringing with themselves a certain message for people of those times and future generations. The witness like that has been for example the great stone which Joshua had set up under an oak in Sichem because of renewal of the covenant between God and Jews. The stone was to remind the Jews about miraculous interventions of Yahweh into the story of the Chosen People, about beautiful declarations, which Jews vowed to God (mostly resignation of worship of foreign gods and abiding the Law, which was to guarantee God's blessing) and about the covenant made.